Choice of Hypnotic Drug for Obstetric and Non-obstetric General Anaesthesia. Comment on Br J Anaesth 2020; 125: e81-7. Issue 2 (June 2021) - Bouvet, L.; Chassard, D.
Abstract : ( Br J Anaesth . 2020;125:e452–e453) Airway management conditions are affected by many factors, including the anesthetic induction drugs used. A recent study by Bonnett and colleagues in patients undergoing non-elective Cesarean delivery found co-administering propofol with succinylcholine resulted in superior intubating conditions compared with the co-administration of thiopental with succinylcholine. These results support the use of propofol rather than thiopental in obstetric general anesthesia.